An algorithm determining (2-d)-kernels in trees - Bednarz, Paweł; Wloch, Iwona (Utilitas Mathematica, 2017)
In this paper we give a complete characterization of trees with (2- d)-kernel using special operations. Moreover we present an algorithm which determines (2-d)-kernel in trees.